Certificate of Accreditation for Programme Corporate Master in Business Administration (CMBA) - Universiti Malaysia Sarawak (Universiti Malaysia Sarawak (UNIMAS), 2013)
Certificate of Accreditation for Programme Corporate Master in Business Administration (CMBA) has attained the quality assurance standards set by the agency and is in compliance with the Malaysian qualifications framework Level 7. Date of Accreditation : 11/09/2013